Optimal heat transfer design for district-heating and cooling pipelines in air-filled cavities - Babus'Haq, Ramiz F. (Cranfield University, 1986)
District-heating and/or cooling systems are gradually becoming popular all over the world for heating and/or cooling of large premises. Current conventional practice for the DHC underground distribution networks is to place the supply and the return pipelines side-by-side in air-filled trencRe's. However, t present investigation has shown that by optimising the location of the pipelines, the thermal insulation provided by the air around the pipes can be maximised. This is achieved by placing the hot pipeline above the cold one, the exact position depending upon the temperatures involved. For most purposes, it is recommended that the displacement ratio for the hot pipe is to be at -0.7 or -0.08 and that of the cold pipe at 0.05 or 0.67 for district heating or cooling respectively [i. e. the hot and cold pipes being placed in the upper and lower halves of the trench respectively]. Each chapter is presented in such a way that it can be read independently of the others as far as possible.